2019
DOI: 10.1111/ijfs.14230
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulation and immune boosting properties of prebiotic dragon fruit oligosaccharides

Abstract: SummaryThis is the first report of the evaluation of suitability for consumption of dragon fruit oligosaccharide (DFO) and its efficacy on gut microbiota modulation and in boosting the gut immune response in rats. The DFO produced significantly increased faecal bifidobacteria and lactobacilli but decreased bacteroides and clostridia. The DFO also showed immune‐response boosting properties by significantly increasing the plasma immunoglobulin A and G concentrations. In addition, it was confirmed by blood chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Peerakietkhajorn et al (2020)'s study demonstrated that dragon fruit oligosaccharides increased the probiotics population (Bifidobacteria, Lactobacilli) in proximal and distal colon of mice. Furthermore, Pansai et al (2019) found immune boosting properties of prebiotic dragon fruit oligosaccharides in animal model.…”
Section: Effect Of Rdf On Wgttmentioning
confidence: 94%
“…Peerakietkhajorn et al (2020)'s study demonstrated that dragon fruit oligosaccharides increased the probiotics population (Bifidobacteria, Lactobacilli) in proximal and distal colon of mice. Furthermore, Pansai et al (2019) found immune boosting properties of prebiotic dragon fruit oligosaccharides in animal model.…”
Section: Effect Of Rdf On Wgttmentioning
confidence: 94%
“…We used scientific and common English names of H. undatus, A. cherimola, C. australasica, and A. carambola as keywords in either title or title and abstract, finding totals of 336, 256, 70, and 329 papers, respectively. Thereafter, subsets of 24,29,17, and 61 papers were selected for H. undatus, A. cherimola, C. australasica, and A. carambola, respectively, concerning traditional uses, phytochemistry, nutritional value, medicinal properties, ethnobotanical uses, experimental studies, and clinical trials.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, nutritional value is conferred by high contents in vitamin C, thiamine, niacin, riboflavin, omega-3 and -6 fatty acids, calcium, phosphorous, and iron [15]. The fruit oligosaccharide has been found to act as prebiotic in mice gut, and to modulate microbiota and stimulate gut immune responses in rats [16,17].…”
Section: Nutritional Valuementioning
confidence: 99%
“…Tremendous evidence has indicated that F&V have manipulating effects on gut microbiota via in vivo and in vitro studies, in animal models or among human volunteers (Klinder et al, 2016;Zhu et al, 2016;Henning et al, 2017;Vivarelli et al, 2017;Choi et al, 2018;Marungruang et al, 2018;Cui et al, 2019;Nagano & Yano, 2019;Wu et al, 2019aWu et al, , 2019bWu et al, , 2019cWu et al, , 2019d. Subsequently, more in-depth investigations on phytochemicals have been carried out, and its correlation with gut microbiota has been explored extensively in recent years (Liu et al, 2018b;Liu et al, 2018a;Pansai et al, 2019;Wei et al, 2019;Wu et al, 2019;Xu et al, 2020;Zhou et al, 2020) (Table 1). Several groups and subgroups of phytochemicals in certain F&V were suggested to modulate specific phylum or species of gut microbes, which include polyphenols, flavonoids, fibres, terpenoids and nitrogencontaining compounds.…”
Section: Gut Microbiota Modulators In Fandvmentioning
confidence: 99%
“…Results indicated that orally ingested pectin for 8 weeks significantly increased the relative abundance of Bacteroides, Parabacteroides, Olsenella and Bifidobacteria in the mice gut. Dragon fruit oligosaccharides exerted comparable impacts on rat gut by increasing faecal Bifidobacteria and Lactobacilli but decreasing Bacteroides and Clostridia (Pansai et al, 2019). Moreover, dragon fruit is a good source of prebiotics since it comprises a large proportion of oligosaccharides that are similar to inulin/fructooligosaccharide, which showed prebiotic properties via in vitro fermentation (Wichienchot et al, 2010).…”
Section: Fibres In Fandvmentioning
confidence: 99%